Rationalizing substituent effects in 1-azathioxanthone photophysics. (19th December 2017) - Junker, Anne Kathrine R; Sørensen, Thomas Just
Abstract: The influence of an electron donating substituent on the photophysical properties of 1-azathioxanthone dyes has been investigated using optical spectroscopy and theoretical models. The motivation behind the study is based on the fact that thioxanthones are efficient triplet sensitizers, and thus promising sensitizers for lanthanide centered emission. By adding an aza group to one of the phenyl ring systems, direct coordination to a lanthanide center becomes possible, which makes azathoixanthones great candidates as antenna chromophores in lanthanide(III) based dyes. Here, three 1-azathioxanthone derivatives have been synthesized targeting efficient triplet formation following absorption in the visible range of the spectrum. This is achieved by adding methoxy groups to the 1-azathioxanthone core. The derivatives were characterized using absorption, emission, and time-gated emission spectroscopy, where fluorescent quantum yields, singlet and triplet excited states lifetimes were determined. The experimentally determined photophysical properties of the three 1-azathioxanthone compounds are contrasted to those of the parent thioxanthone and is rationalized using the Strickler–Berg equation, Hückel MO theory, and Dewar's rules in combination with computational chemistry. We find that the transition energies follow predictions, but that the overall photophysical properties are determined by the relative energies as well as the nature of the involved states in both the singlet and the triplet excited state manifolds.